The association of workforce configurations with length of stay and charges in hospitalized patients with congestive heart failure - Williams, Tremaine B.; Crump, Alisha; Parker, Pearman; Garza, Maryam Y.; Seker, Emel; Swindle, Taren Massey; Robins, Taiquitha; Price, Adrian; Sexton, Kevin Wayne (Frontiers in Health Services, 2024)
IntroductionClinicians are the conduits of high-quality care delivery. Clinicians have driven advancements in pharmacotherapeutics, devices, and related interventions and improved morbidity and mortality in patients with congestive heart failure over the past decade. Yet, the management of congestive heart failure has become extraordinarily complex and has fueled recommendations from the American Heart Association and the American College of Cardiology to optimize the composition of the care team to reduce the health, economic, and the health system burden of high lengths of stay and hospital charges. Therefore, the purpose of this study was to identify the extent to which specific care team configurations were associated with high length of stay and high-charge hospitalizations of patients with congestive heart failure.MethodsThis study performed a retrospective analysis of data extracted from the electronic health records of 3,099 patients and their hospitalizations from the Arkansas Clinical Data Repository. The data was analyzed using binomial logistic regression in which adjusted odds ratios reflected the association of specific care team configurations (i.e., combination of care roles) with length of stay and hospital charges.ResultsTeam configurations that included a nurse practitioner, registered nurse, care manager, and social worker were generally above the median length of stay and median charges when compared to team configurations that did not collectively include all of these roles. Patients with larger configurations (i.e., four or more different care roles) had higher length of stays and charges than smaller configurations (i.e., two to three different care roles). The results also validated the Van Walraven Elixhauser Comorbidity Score by finding that its quartiles were associated with length of stay and charges, an indicator of care demand based on patient morbidity.ConclusionsCardiologists, alone, cannot shoulder the burden of improving patient outcomes. Care team configuration data within electronic health record systems of hospitals could be an effective method of isolating and tracking high-risk patients. Registered nurses may be particularly effective in advancing real-time risk stratification by applying the Van Walraven Elixhauser Comorbidity Score at the point of care, improving the ability of health systems to match care demand with workforce availability.